2016
DOI: 10.1177/0192623316637708
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes in the Nasal Cavity after N, N-dimethyl-p-toluidine Exposure

Abstract: N,N-Dimethyl-p-toluidine (DMPT) (Cas No. 99-97-8), an accelerant for methyl methacrylate monomers in medical devices, is a nasal cavity carcinogen in a 2-year cancer study in male and female F344/N rats, with the nasal tumors arising from the transitional cell epithelium. In this study we exposed male F344/N rats for five days to DMPT (0, 1, 6, 20, 60 or 120 mg/kg (oral gavage)) to explore early changes in the nasal cavity after short-term exposure. Lesions occurred in the nasal cavity including hyperplasia of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Nrf2 antioxidant responses occur after exposure to other liver toxins including aflatoxin (Kensler et al 2014; Merrick et al 2012; Singh et al 2015) and carbon tetrachloride (Chen et al 2014), and are found in other organ toxicities including in the lung (Cho et al 2015) and nasal cavity (Dunnick et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 antioxidant responses occur after exposure to other liver toxins including aflatoxin (Kensler et al 2014; Merrick et al 2012; Singh et al 2015) and carbon tetrachloride (Chen et al 2014), and are found in other organ toxicities including in the lung (Cho et al 2015) and nasal cavity (Dunnick et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Nanostring Analysis: NanoString nCounter (NanoString, Seattle, WA, USA) was used as a multiplexed gene expression platform to test for specific transcripts as previously described [ 104 ]. Briefly, non-cross-reactive probes were custom synthesized and mixed to validate transcript expression after normalization with housekeeping transcripts ( Actb ; Gapdh , Hprt , Rpl32 ) that were determined by RNA-seq to be treatment stable.…”
Section: Methodsmentioning
confidence: 99%